A Prospective Comparative Study of Rituximab Monotherapy and Dexamethasone-Cyclophosphamide Pulse Therapy in Patients Diagnosed with Pemphigus vulgaris - Saha, Rametrika; Biradar, Veeranagoud; Konkani, Spoorti; Reddy, Mandati Santhosh; Doshi, Bhavana (International Journal of Pharmaceutical Investigation, 2026)
Background Pemphigus vulgaris (PV) is a severe autoimmune blistering disorder traditionally managed with corticosteroids, which are associated with significant adverse effects; as a result, alternative therapies such as Rituximab and Dexamethasone-Cyclophosphamide Pulse (DCP) therapy have gained clinical relevance. Objectives To compare the clinical outcomes, safety profiles, and quality-of-life improvements achieved with Rituximab versus DCP therapy over a 9-month follow-up period. Materials and Methods A prospective observational study was conducted at a tertiary care centre involving 76 patients diagnosed with PV. Of these, 40 received DCP therapy and 36 were treated with Rituximab. The DCP regimen consisted of dexamethasone 100 mg IV for three consecutive days monthly, cyclophosphamide 500 mg IV monthly, and 50 mg oral cyclophosphamide daily (Phase I). Rituximab was administered following the rheumatoid arthritis protocol (1 g IV on days 1 and 15). Outcomes including remission, recurrence, Adverse Drug Reactions (ADRs), and Dermatology Life Quality Index (DLQI) scores were assessed at baseline and at 1, 3, 6, and 9 months. Results Rituximab showed a 42% lower risk of recurrence compared with DCP. ADRs in the Rituximab group were mainly mild and self-limiting infusion-related rashes, while DCP therapy was associated with transient hyper-glycaemia and a slightly higher rate of infections. By 9 months, ADR incidence declined to 30% in the DCP group and 8.33% in the Rituximab group. Clinical response assessment included new lesion formation, healing rate, body surface area involvement, mucosal changes, and recurrence patterns. DLQI scores improved significantly in both groups, with greater improvement in the Rituximab group (16.00 to 4.00) compared with DCP (14.50 to 5.50) (p=0.019). Conclusion Rituximab demonstrated faster clinical improvement and superior quality-of-life outcomes at 9 months. However, the limited duration of follow-up restricts conclusions about long-term relapse-free remission.
Keywords: Dermatology Life Quality Index; Dexamethasone-cyclophosphamide Pulse; Pemphigus vulgaris; Pulse therapy; Rituximab